1988
DOI: 10.2307/3577203
|View full text |Cite
|
Sign up to set email alerts
|

Human Epithelial Teratocarcinoma Cells (P3): Radiobiological Characterization, DNA Damage, and Comparison with Other Rodent and Human Cell Lines

Abstract: Survival parameters and immediate DNA damage induced by 60Co gamma rays, 50-kVp X rays, and Janus fission-spectrum neutrons in human epithelial P3 cells (derived from an embryonic teratocarcinoma) are compared with those for Chinese hamster lung V79 cells. DNA damage caused by X and gamma irradiation, measured by alkaline elution methods, is the same in both cell types, whereas the P3 cells are about two times more sensitive (as measured by Do ratios of the final survival curve slope) to the lethal effects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

1988
1988
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“…Only one study is available concerning the induction of the medium transfer bystander eff ect and direct eff ect by low doses of neutrons (Liu et al 2006, and PhD thesis Liu, personal communication). It is well known that neutron radiation is signifi cantly more effi cient than gamma rays in killing cells and inducing chromosomal aberrations, gene mutations and oncogenic transformation (Field 1976, Hill et al 1988, Peak et al 1991. However, neutron radiation is always contaminated by a contribution from gamma radiation.…”
Section: Introductionmentioning
confidence: 99%
“…Only one study is available concerning the induction of the medium transfer bystander eff ect and direct eff ect by low doses of neutrons (Liu et al 2006, and PhD thesis Liu, personal communication). It is well known that neutron radiation is signifi cantly more effi cient than gamma rays in killing cells and inducing chromosomal aberrations, gene mutations and oncogenic transformation (Field 1976, Hill et al 1988, Peak et al 1991. However, neutron radiation is always contaminated by a contribution from gamma radiation.…”
Section: Introductionmentioning
confidence: 99%
“…1987, Hill et al . 1988) by comparison with the elution of DNA from cells irradiated with 3 .0 Gy of 50-kVp X-rays .…”
Section: Strand Breakage Calculationsmentioning
confidence: 95%
“…The alkaline elution assay was performed as described by Kohn et al . (1981), procedure B, and by Hill et al . (1988) .…”
Section: Alkaline Elutionmentioning
confidence: 95%
See 1 more Smart Citation
“…The numbers of breaks induced in the DNA of human cells in culture by monochromatic 334nm radiation in the presence and absence of CPZ (200 pM) were calculated from the slopes of the elution profiles as described (Kohn et al, 1981) with an X-irradiated (3Gy) standard; 3 Gy of X-rays have been shown to induce 8.1 SSB per 1010 daltons in human cells (Hill et al, 1988).…”
mentioning
confidence: 99%